ANALISIS PERTANGGUNGJAWABAN SUBJEK HUKUM PERDATA TERHADAP KONTRAK YANG DIBUAT DENGAN BANTUAN KECERDASAN BUATAN DI INDONESIA - NIM. A1011211162, MUHAMMAD SALMAN ALFARISI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This research examines the legal problem concerning the uncertainty of civil liability for contracts created with the assistance of artificial intelligence (AI) in Indonesia. As the adoption of AI in automating legal document drafting increases, issues arise regarding the validity and allocation of responsibility when errors or losses occur. The research question is: what is the form of civil liability for contracts drafted with AI assistance? This study aims to analyze the legal certainty of the legality and validity of AI-based contracts under Indonesian positive law, and to identify the forms of liability for the parties involved